Meme-ingful Actions: Uncovering the Influence of Political Memes on Leadership Performance and Values Formation - G. Matias, Nicole Andrea; D. Bartolome, Prince Henderson; R. Carreon , Samantha Louise; L. Tallara, Franz Marielle; A. Villarama, Joseph (Language, Technology, and Social Media, 2024)
Political memes circulate all over the digital world, exerting a profound influence on the political engagement of leaders. This study focused on identifying the influence of political memes on the political engagement of college student-leaders and explored the subsequent effects on their leadership performance and values formation. Grounded on Bandura’s Social Learning Theory, this phenomenological study interviewed with ten open-ended questions, 15 college student-leaders (CSLs) from Central Luzon State University, Philippines. The data gathered underwent through Colaizzi’s thematic analysis and were verified through data cross-checking. Results revealed that political memes have a significant influence on the opinion of student-leaders in the digital media, serving as one of the motivators for CSLs’ engagement in political movements and activities. Despite the condensed information of memes, their widespread scope and entertainment mobilizes political discourse across social media. Thus, social media plays a crucial role in guiding leaders’ political involvement, highlighting the importance of digital literacy in educating leaders for future generations. CSLs’ interest in media entertainment and collective action reflects in the influence of political memes, shaping discourse and mobilizing peers, as a humorous and informative medium for driving societal change and directing political movements.